Implicaciones Clínico-Patológicas de la expresión del receptor KIT Y PD-ECGF en cáncer de cuello uterino (2015)
Objective: To establish the expression of KIT receptor and PD-ECGF as predictive factors for treatment response in cervical cancer. Methods: A prospective and observational study was design. KIT receptor and PD-ECGF were detected by immunohistochemistry on the cervical biopsies. Imagenologic and clinical response to concurrent radiotherapy and chemotherapy was evaluated. Results: Forty five patients were studied. 68, 3% were squamous carcinomas and 51, 1% were in clinical stage IIB. 77, 8% (n=32) had complete response to treatment. Two patients (4, 4%) showed positivity to the expression for KIT receptor. 93, 3% of the samples were positive for the expression of PD-ECGF. There were no statistical correlation between the expression of the proteins and the variables studied. Conclusions: KIT receptor and PD-ECGF did not show utility as predictive factors for treatment response in cervical cancer.